Development of Final Year Project Supervisor Selection System for FSKTM, UTHM - Tam, Jin Horng; Abdullah, Noryusliza (Applied Information Technology And Computer Science, 2025)
Selecting a suitable supervisor for the final year project is a crucial starting point for producing a satisfying and perfect project; the right supervisor provides valuable guidance to help students. However, the Faculty of Computer Science and Information Technology at University Tun Hussein Onn still relies on manual selection methods, which leads to time-consuming and mismatched student research and supervisor expertise. Therefore, a comprehensive website is developed to handle the student’s application request and the supervisor’s response while simplifying the process of finding a supervisor. The development of the system is highly dependent on the agile methodology, which focuses on stakeholders’ requirements and involvement. This system was developed in a client-server structure that provides a seamless user experience for different devices. This system is expected to enhance efficiency and make the supervisor selection process convenient. It also helps the faculty coordinator easily monitor the latest supervisor-student matching information.